Evolution of quality standards in plant cryobanks - The International Potato Center as a case study - Vollmer, R.; Ellis, David; Barkley, N.A. (Elsevier, 2018)
The International Potato Center holds one of the largest and most diverse potato cryobanks worldwide. The cryo-collection includes 1855 landraces, belonging to seven potato species and four different ploidy levels. The potato cryo-collection was principally built up in recent years (2013-17), under strict quality and operative standards. The average regrowth rate of the potato cryo-collection is 58% and 1234 of 1855 accessions showed a regrowth rate of 50% or higher. The success rate, i.e. the percent of successfully cryopreserved accessions (minimum 20% of regrowth) in relation to the totally processed accessions has increased in 2016 to 95.4%. Real time data record of each step of the process with pocket PCs and bi-dimensional cryo-resistant barcode labels is an important part of our cryo-system. Full plant recovery (+LN) as standard parameter for regrowth assessment, a large-scale applicable cryo-protocol (high success rate), systematic viability reassessment, clear threshold of minimum acceptable regrowth (30%: one single cryo-run, 20-30%: two independent cryo-runs, <20%: accession was discarded and not transferred to the cryobank), a high sample size (20%) for initial regrowth assessment, safety back-up of cryobanked accessions, performance indicators of the cryo-staff, and a continuous electronical monitoring of the correct temperature within the cryotanks are other important features of the system. It was concluded that the International Potato Center has built up a quality system for cryobanking that has integrated the key components for good cryobanking of Plant Genetic Resources.